Properties of an ideal burn dressing: A survey of burn survivors and front-line burn healthcare providers. Issue 2 (March 2019) - Carta, T.; Gawaziuk, J.P.; Diaz-Abele, J.; Liu, S.; Jeschke, M.; Logsetty, S.
Highlights: Current burn dressings are imperfect. Burn care providers and burn survivors rank burn dressing properties differently. Development of burn dressings should consider patient and caregiver perspectives. Abstract: Objectives: The objective of this study is to identify what burn survivors and front-line staff indicate would improve satisfaction with burn dressings, and the ranking of importance of different burn dressing characteristics. These findings will guide the development of future dressings to meet these needs. Methods: Burn survivors (including the person injured and their family) and front-line burn healthcare providers completed a questionnaire on the importance given to different burn dressing characteristics (non-stick, absorbent, able to wear for a long time, flexible, easy to put on, easy to take off, antimicrobial, and non-bulky), and about the adequacy of pain management during dressing changes. Results: A total of 99 individuals filled out the questionnaire (31 caregivers/survivors and 68 front-line burn healthcare providers). The most important dressing characteristics by both groups were "non-stick" and "fights infection". There was a significant difference between burn survivors and front-line burn healthcare providers pertaining to adequacy of pain management during dressing change. Adequate pain management was reported by 59% of burn survivors, which was significantly higher than that reported by the 25% front-line burn healthcare providers (p = 0.002). Conclusions: Our study suggests that burn survivors and front-line burn providers have similar views on what constitutes an ideal dressing. A significantly proportion of caregiver/survivors felt that pain associated with dressing changes is being adequately managed despite healthcare providers' perception.